Cooperatives, Grassroots Development, and Social Change : Experiences from Rural Latin America - Finan, Timothy J. (Book collections on Project MUSE., 2017)
"Cooperatives, Grassroots Development, and Social Change" presents examples from Paraguay, Brazil, and Colombia, examining what is necessary for smallholder agricultural cooperatives to support holistic community-based development in peasant communities. Reporting on successes and failures of these cooperative efforts, the contributors offer analyses and strategies for supporting collective grassroots interests. Illustrating how poverty and inequality affect rural people, they reveal how cooperative organizations can support grassroots development strategies while negotiating local contexts of inequality amid the broader context of international markets and global competition. The contributors explain the key desirable goals from cooperative efforts among smallholder producers. They are to provide access to more secure livelihoods, expand control over basic resources and commodity chains, improve quality of life in rural areas, support community infrastructure, and offer social spaces wherein small farmers can engage politically in transforming their own communities. The stories in "Cooperatives, Grassroots Development, and Social Change" reveal immense opportunities and challenges. Although cooperatives have often been framed as alternatives to the global capitalist system, they are neither a panacea nor the hegemonic extension of neoliberal capitalism. Through one of the most thorough cross-country comparisons of cooperatives to date, this volume shows the unfiltered reality of cooperative development in highly stratified societies, with case studies selected specifically because they offer important lessons regarding struggles and strategies for adapting to a changing social, economic, and natural environment.